Utilization Of Zeliac As An Alternative Adsorbent To Remove Low Level Concentration Of Nom In Riverbank Filtration - Ibrahim, Nurazim (2018)
An increase of NOM in river water is a concern as it is the main precursor to health hazard disinfection by-products (DBPs) in conventional drinking water treatment system. River bank filtration (RBF) is a good option to reduce surface water pollution and overcome water shortage problem especially during extreme weather events such as droughts and floods. Therefore, this study aims to reduce the possibility of DBPs formation by controlling the level of NOM and treating it together with bio-colloids and ionic pollutant by composite adsorbent Zeliac in RBF. Water quality monitoring study shows that NOM in Kerian River recorded an average of 3.6 mg/L DOC and 0.10 cm-1 UV254. Total coliform exceeded the raw water quality standard with an average concentration of 1.5x104 MPN/100 mL. The same mean level of UV254 (0.03 cm-1) was determined in the water from RBF and LBWTP. Meanwhile, higher level of DOC measured from final treated water (1.6 mg/L) than RBF (0.81 mg/L). For bio-colloids in RBF, no E. coli was present but total coliform was still detected in the water. Other determined parameters were also reduced except for Fe and Mn. This finding signifies the water abstracted from RBF well still requires further treatment to ensure the water is safe and clean for human consumption. The characteristics study of Zeliac shows that the adsorbent has a surface area of 40.6 m2/g and average pore size of 16.5 nm. The existence of Ca, Si and Al makes Zeliac a good cations exchanger. In addition, hydroxyl and carboxyl groups proved that Zeliac can attract positive ions or anionic organic pollutants depending on the water sample acidity. According to the equilibrium and kinetic study, the removal of pollutants was controlled by multilayer adsorption onto heterogeneous surface of Zeliac. At optimum dosage of 7 g per 100 mL sample, the removal efficiency of UV254, colour and NH3-N were 72.8% (0.129 – 0.035 cm-1), 78.6% (42 - 9 PtCo) and 77.1% (0.70 – 0.16 mg/L), respectively. In column adsorption experiments, it was found that granular size of Zeliac gave no significant effect to the removal performance. The break point for UV254 and bio-colloids occurred at 103 and 31 hours of experiment respectively at hydraulic loading rate of 1 cm/min. These results show a good performance of Zeliac in removing both organic and ionic compounds in drinking water source as well as its capability as an alternative filter media in the RBF.